A Comprehensive Analysis of Phishing Challenges and Ai Solutions Adopted by it Organizations - S. Harihar, Sanjog; Potdar, Mahesh (Journal of Neonatal Surgery, 2025)
One of the most persistent and dynamic dangers to IT firms globally is still phishing. As cutting-edge technology like artificial intelligence (AI) have become more prevalent, cybersecurity has experienced both advancements and new difficulties. Although AI-powered solutions have improved security, hackers are also using AI to craft extremely dishonest and focused phishing attacks. This study looks at the most recent phishing risks that IT companies must deal with, such as deepfake schemes, Business Email Compromise (BEC), AI-powered attacks, and the abuse of reliable platforms. It also looks at how IT companies are utilizing AI-powered solutions to counter these dangers. This study illustrates how businesses are bolstering their defences by inspecting the efficacy of machine learning, natural language processing, and real-time threat detection. The findings objective is to provide a deeper understanding of the constantly changing phishing landscape and offer strategic insights for building more adaptive, scalable, and proactive cybersecurity frameworks